Rationale and indications for coronary chronic total occlusion interventions. Issue 1 (December 2015) - Vo, M. N.; Rinfret, S.
Abstract: Chronic total occlusions (CTOs) are commonly found in patients with coronary artery disease and are considered the "final frontier" of coronary intervention. Despite growing interest in percutaneous coronary intervention (PCI) of CTOs along with advances in techniques and equipment, attempt rates remain low. This is most likely due to the fact that CTO PCI remains technically challenging and requires higher resource utilization. Furthermore, there remains controversy regarding the actual clinical benefit of successful CTO PCI. However, there have been a growing number of studies reporting short‐ and long‐term outcomes of CTO revascularization. We therefore sought to review the evidence and potential clinical benefits of successful CTO PCI. Answer questions and earn CME: https://www.wileyhealthlearning.com/Activity2/3691380/Activity.aspx